Effect of Health Shocks on Poverty Status in South Korea: Exploring the Mechanism of Medical Impoverishment - Chang-O Kim (Kerman University of Medical Sciences, 2022)
Background  South Korea has the highest out-of-pocket burden for medical expenses among the Organisation for Economic Co- operation and Development (OECD) member countries and has no formal sickness benefit system, along with United States and Switzerland, greatly increasing the risk of poverty due to a sudden illness. Methods  We identify the causal effect of health shocks on poverty status and explore the mechanisms of medical impoverishment by analyzing longitudinal data from 13 670 households that participated in the representative Korean Welfare Panel Study (KOWEPS) from 2007 to 2016. In this study, we define a health shock as a case in which no household members were hospitalized in the previous year, but together they had more than 30 days of hospitalization in this year. The propensity score matching method was combined with a mediation analysis in this work. Results  The proportion of households in absolute poverty increased by 4.6-8.0 percentage points among households that experienced a health shock compared with matched controls. The selection effects due to health shock were estimated to be 5.6-8.2 percentage points. On average, a sudden hospitalization reduces annual non-medical expenditures and equivalized disposable income by just over 3.2 million KRW (2500 USD) and 1.2 million KRW (1000 USD), respectively. Health shock induces impoverishment after one year through both the medical expense and work capacity pathways, which explain 12.8% and 12.8% of the total effect, respectively. However, when we decompose the mediation effect of a health shock on poverty status after two years, we find that a health shock leads to poverty mainly through labor force nonparticipation (9.9%). Conclusion  Income stabilizing scheme to protect households that experience a health shock should be introduced as a policy alternative to confront the issue of medical impoverishment.